Factors associated with utilization of neoadjuvant chemotherapy in charlson comorbidity zero non-metastatic muscle-invasive bladder cancer patients - Au, Daniel; Lee, Eugene K.; Popoola, Taiye O.; Parker, William P.; Onge, Jarron M. Saint; Ellis, Shellie D. (International Brazilian Journal of Urology, 2021)
Guideline-based best practice treatment for muscle invasive bladder cancer (MIBC) involves neoadjuvant chemotherapy followed by radical cystectomy (NACRC). Prior studies have shown that a minority of patients receive NACRC and older age and renal function are drivers of non-receipt of NACRC. This study investigates treatment rates and factors associated with not receiving NACRC in MIBC patients with lower comorbidity status most likely to be candidates for NACRC. Retrospective United States National Cancer Database analysis from 2006 to 2015 of MIBC patients with Charlson comorbidity index (CCI) of zero. Analysis of NACRC treatment trends in higher CCI patients was also performed. 15.561 MIBC patients met inclusion criteria. 1.507 (9.7%) received NACRC within 9 months of diagnosis. NACRC increased over time (15.0% in 2015 compared to 3.6% in 2006). Higher NACRC was noted in females, cT3 or cT4 cancer, later year of diagnosis, and academic facility treatment. Lower utilization was noted for blacks and NACRC decreased with increasing age and CCI. Only 16.9% of patients aged 23-62 in the lowest age quartile with muscle invasive bladder cancer and CCI of 0 received NACRC. Although utilization is increasing, receipt of NACRC remains low even in populations most likely to be candidates. Further study should continue to elucidate barriers to utilization of NACRC.